2022
DOI: 10.1039/d2ob01918c
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in pyrazole synthesis employing diazo compounds and synthetic analogues

Abstract: Pyrazole is an essential structural component of many pharmaceuticals and agrochemicals. The synthesis of pyrazoles has been a subject of intense research for several decades. Many transformations are now available...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 158 publications
0
15
0
Order By: Relevance
“…1 In this context, tremendous efforts have been devoted to the development of robust and versatile synthetic methods to incorporate a single fluorine atom or fluoroalkyl groups into pyrazole rings. 2,3 In sharp contrast, the synthesis of pyrazoles bearing two different fluorinated groups remains underdeveloped, 4 despite their potentially enhanced potency in drug discovery. Leroux and co-workers described several facile strategies to synthesize a diverse set of bis(fluoroalkyl)pyrazoles based on fluoroalkyl amino reagents (FARs).…”
Section: Introductionmentioning
confidence: 99%
“…1 In this context, tremendous efforts have been devoted to the development of robust and versatile synthetic methods to incorporate a single fluorine atom or fluoroalkyl groups into pyrazole rings. 2,3 In sharp contrast, the synthesis of pyrazoles bearing two different fluorinated groups remains underdeveloped, 4 despite their potentially enhanced potency in drug discovery. Leroux and co-workers described several facile strategies to synthesize a diverse set of bis(fluoroalkyl)pyrazoles based on fluoroalkyl amino reagents (FARs).…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic strategies towards F-containing heterocycles, including cycloadditions and cyclocondensation reactions, functional group interconversions, and catalytic C–H functionalizations, have been developed in recent decades and are nicely summarized elsewhere [ 15 , 16 , 17 , 18 ]. In this context, there is increasing interest in the chemistry of fluoroalkylated 1,3-dipoles, which are recognized as highly useful building blocks for Huisgen (3+2)-cycloaddition reactions [ 19 , 20 , 21 , 22 , 23 , 24 ]. For example, despite some limitations and the difficult handling of 2,2,2-trifluorodiazoethane, this highly reactive intermediate has been extensively explored, not only as 1,3-dipolar reagent, but also as a valuable source of the respective carbene employed in (2+1)-annulation reactions [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, there is increasing interest in the chemistry of fluoroalkylated 1,3-dipoles, which are recognized as highly useful building blocks for Huisgen (3+2)-cycloaddition reactions [ 19 , 20 , 21 , 22 , 23 , 24 ]. For example, despite some limitations and the difficult handling of 2,2,2-trifluorodiazoethane, this highly reactive intermediate has been extensively explored, not only as 1,3-dipolar reagent, but also as a valuable source of the respective carbene employed in (2+1)-annulation reactions [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diazo-carboxylic esters are commonly used electron-deficient 1,3-dipoles in these [3+2] cycloaddition reactions. 3,4 For example, a diazo-carboxylic ester and an electron-rich olefin, such as an enamine, can react to form a pyrazole ring. 4 This reaction was originally proposed to proceed via a concerted mechanism.…”
mentioning
confidence: 99%
“…3,4 For example, a diazo-carboxylic ester and an electron-rich olefin, such as an enamine, can react to form a pyrazole ring. 4 This reaction was originally proposed to proceed via a concerted mechanism. However, recent studies showed that this reaction may proceed through a stepwise pathway (Scheme 1), starting with a nucleophilic addition of the enamine olefinic carbon onto the terminal nitrogen of the diazo motif, where the nucleophilicity of the dipolarophile and the electrophilicity of the 1,3-dipole are crucial.…”
mentioning
confidence: 99%